Gendered archetypes of wartime occupation: 'New women' in occupied north China, 1937-1940 - Taylor, Jeremy E. (Wiley, 2016)
This article examines the creation and use of gendered archetypes by the Provisional Government of the Republic of China (PGROC), the first collaborationist government established in China following the Japanese invasion of 1937. Drawing on a wide range of visual sources, it traces how this regime's messages about where women ‘belonged’ in an occupied China resulted in the creation of unique and complex archetypes which were deployed to convince Chinese women of the advantages of PGROC rule. Chief among these archetypes was the figure of the ‘PGROC new woman’. I show how this figure developed in PGROC poster art and propaganda, and eventually in film, as well as how it evolved out of early wartime and pre-war precedents. In addition to detailing the uses and meanings of this (and other) archetypes, the article suggests that comparative analyses of gendered archetypes of collaboration developed in cognate regimes during the same period can help shed light on the extent to which the peculiar circumstances of wartime collaboration often resulted in specific ideas by male collaborationist leaders about the roles women were expected to play under occupation.